Campur Kode Bahasa Buton Terhadap Bahasa Indonesia Pada Rapat Organisasi Himpunan Mahasiswa Buton di Kota Samarinda - Samiun, Samiun; Mursalim, Mursalim; Ahmad, M. Rusydi (Universitas Mulawarman, 2019)
The purpose of this study was to describe the form and factors causing code mixing at the Buton Student Association Organization Meeting in the city of Samarinda. This research uses the matching and agih method. The data collection technique used the listening method and the speaking method. The results of the study show the form of code mixing between Butonese and Indonesian at the Buton Student Association Organization Meeting in the city of Samarinda and the factors that cause code mixing. The forms of Code Mixing are 1) Code Mixing in the form of words, 2) Code Mixing in the form of phrases, 3) Code Mixing in the form of clauses. There are 2 factors that cause code mixing, namely 1) the speaker factor, 2) the language factor. From the results of this study, it can be concluded that the communication process that occurs at the Buton Student Association Organization Meeting in the city of Samarinda is in the form of code mixing in the form of words, phrases and clauses. Factors causing code mixing are speaker factors and language factors.